Engineered MoSe2/WSe2 based heterostructures for efficient hydrogen evolution reaction. (2021) - Rahul,; Singh, Harpreet; Lalla, N.P.; Deshpande, Uday; Arora, Sunil Kumar
Abstract: Electrocatalytic water splitting into hydrogen and oxygen using semiconducting heterogeneous nanostructures is a promising and emerging technology. Semiconductor materials based heterogeneous nanostructures have attracted much attention to be used as catalysts, co-catalysts, photocatalysts and photo absorbers. The present work deals with the investigation of heterostructures of molybdenum selenide (MoSe2 ) and tungsten selenide (WSe2 ) nanosheets prepared through liquid exfoliation method as electrocatalysts for the hydrogen evolution reaction (HER). Our experimental studies reveal that MoSe2 /WSe2 heterostructures synthesized using hydrogen peroxide (H2 O2 ) exhibits superior HER performance. These novel structures leads to the exposure of more catalytically active sites and maintains effective electron transport, resulting in a small Tafel slope of 80 mV/decay and large electrochemical surface area (ECSA) of 87. This low-cost method finds application in high-performance HER electrocatalyst.